Peran Hipertensi sebagai Faktor Risiko Terjadinya Gagal Ginjal Kronik - Novita Rachmasari; Mhd. Teguh Asyraf (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
The prevalence of chronic kidney disease continues to increase in Indonesia and ranks second after heart disease. Hypertension is one of the dominant factors causing chronic kidney disease. This study aims to analyze the relationship between hypertension and the risk of chronic kidney disease. The method used is a Systematic Literature Review (SLR) by reviewing articles from accredited national journals (SINTA) and international journals indexed in Scopus published between 2020 and 2025. The results of the analysis show that hypertension is significantly associated with the risk of chronic kidney disease. The underlying mechanism of hypertension and chronic kidney disease is through the activation of the renin-angiotensin-aldosterone system (RAAS).